Romantic irony in drama «Don Juan» J. Byron - Рева, Ірина Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals concept and specificity of romanticism such as a literary movement. The sings leading romantic hero have been determined in the works of J. G. Byron. The image of hero and author has been compared in drama «Don Juan» J. G. Byron. The contribution of the artist has been noted in the development of genre lyric drama. The particular attention has been paid the category of «romantic irony» and their means of expression in drama «Don Juan» J. G. Byron. The dedicated and described types of irony have been used in writers work. The specified genre sings lyrical drama and features of individual style of the writer have been based on the study of romantic irony. The creativity of J. G. Byron has been considered in the context of English and European Romanticism. The influence of the artistic discoveries of the artist has been developed in the further literary movement.